DNA methylation in primary myelofibrosis is partly associated with driver mutations and distinct from other myeloid malignancies - Esra Dursun Torlak; Vithurithra Tharmapalan; Kim Kricheldorf; Joelle Schifflers; Madeline Caduc; Martin Zenke; Steffen Koschmieder; Wolfgang Wagner (Clinical Epigenetics)
Abstract Background Primary myelofibrosis (PMF) is a clonal blood disorder characterized by mutually exclusive driver mutations in JAK2, CALR, or MPL genes. So far, it is largely unclear if the driver mutations have a specific impact on DNA methylation (DNAm) profiles and how epigenetic alterations in PMF are related to other myeloid malignancies. Results When we compared DNAm profiles from PMF patients we found very similar epigenetic modifications in JAK2 and CALR mutated cases, whereas MPL mutations displayed less pronounced and distinct patterns. Furthermore, induced pluripotent stem cell (iPSC) models with JAK2 mutations indicated only a moderate association with PMF-related epigenetic changes, suggesting that these alterations may not be directly driven by the mutations themselves. Additionally, PMF-associated epigenetic changes showed minimal correlation with allele burden and seemed to be largely influenced by shifts in the cellular composition. PMF DNAm profiles compared with those from other myeloid malignancies—such as acute myeloid leukemia, juvenile myelomonocytic leukemia, and myelodysplastic syndrome—showed numerous overlapping changes, making it difficult to distinguish PMF based on individual CpGs. However, a PMF score created by combining five CpGs was able to discern PMF from other diseases. Conclusion These findings demonstrate that PMF driver mutations do not directly evoke epigenetic changes. While PMF shares epigenetic alterations with other myeloid malignancies, DNA methylation patterns can distinguish between PMF and related diseases.